2018
DOI: 10.1111/psyp.13069
|View full text |Cite
|
Sign up to set email alerts
|

Event‐related potentials of emotional and neutral memories: The role of encoding position and delayed testing

Abstract: Previous research found that memory is not only better for emotional information but also for neutral information that has been encoded in the context of an emotional event. In the present ERP study, we investigated two factors that may influence memory for neutral and emotional items: temporal proximity between emotional and neutral items during encoding, and retention interval (immediate vs. delayed). Forty-nine female participants incidentally encoded 36 unpleasant and 108 neutral pictures (36 neutral pictu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 63 publications
0
17
1
Order By: Relevance
“…This also implies that untrustworthy faces do not necessarily need to be stored in a more complex contextual fashion (e.g., recollection) when the evolutionary purpose is to quickly recognize socially relevant information. Interestingly, contrary to prior ERP studies using emotional scenes 38,58 or faces 45 , we did not find a modulation in the recollection-sensitive parietal old/new effect. However, emotional scenes and faces contain more contextual feature information and draw more attention 59,60 than neutral faces, which may have resulted in enhanced recollection-specific contextual binding 61 and enhanced parietal ERP old/new differences in these studies.…”
Section: Discussioncontrasting
confidence: 99%
“…This also implies that untrustworthy faces do not necessarily need to be stored in a more complex contextual fashion (e.g., recollection) when the evolutionary purpose is to quickly recognize socially relevant information. Interestingly, contrary to prior ERP studies using emotional scenes 38,58 or faces 45 , we did not find a modulation in the recollection-sensitive parietal old/new effect. However, emotional scenes and faces contain more contextual feature information and draw more attention 59,60 than neutral faces, which may have resulted in enhanced recollection-specific contextual binding 61 and enhanced parietal ERP old/new differences in these studies.…”
Section: Discussioncontrasting
confidence: 99%
“…As in Experiment 1 the study phase was immediately followed by the test phase, it could be the case that the EEM effect would emerge if longer study-test intervals were implemented (Sharot and Phelps, 2004; Mitchell et al, 2006; Sharot and Yonelinas, 2008; Schaefer et al, 2011; Yick et al, 2015), consistent with consolidation processes (Hamann, 2001; Talmi, 2013). However, previous studies also indicated that even in immediate conditions, negative arousing stimuli can be better recognized than neutral stimuli (e.g., Wirkner et al, 2018). Whereas in Experiment 2 stimuli were controlled for arousal, in Experiment 1 both negative and positive stimuli had higher arousal ratings than neutral ones (according to Soares et al, 2012).…”
Section: Discussionmentioning
confidence: 95%
“…It takes the form of more positive going waveforms for hits than correct rejections between 500 and 700 ms, which are most pronounced at (left) parietal recording sites. Interestingly, this parietal old/new effect for recollection has previously been found to be modulated by emotion (Maratos & Rugg, 2001;Ventura-Bort et al, 2016;Weymar et al, 2011;Wirkner et al, 2018), for example with a parietal old/new effect for emotional, negatively-valenced, but not neutral faces (Johansson et al, 2004).…”
Section: Neurophysiological Correlates Of Emotional Item Memorymentioning
confidence: 78%